2019
DOI: 10.1016/j.acra.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Molecular Subtype Prediction by Mammographic Radiomic Features

Abstract: Our study showed that quantitative radiomic imaging features of breast tumor extracted from digital mammograms are associated with breast cancer subtypes. Future larger studies are needed to further evaluate the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 21 publications
2
59
0
1
Order By: Relevance
“…Quantitative features of radiomics can distinguish between TNBC and non-TNBC in mammograms, as has been shown in some studies (19,20). Recently, the relationship between mammographic radiomic features and molecular subtypes of breast cancer was evaluated, which showed that quantitative radiomics imaging features were associated with breast cancer subtypes (21). However, no studies have explored the relationship between TIL levels and the characteristics of mammograms of TNBC patients.…”
Section: Introductionmentioning
confidence: 93%
“…Quantitative features of radiomics can distinguish between TNBC and non-TNBC in mammograms, as has been shown in some studies (19,20). Recently, the relationship between mammographic radiomic features and molecular subtypes of breast cancer was evaluated, which showed that quantitative radiomics imaging features were associated with breast cancer subtypes (21). However, no studies have explored the relationship between TIL levels and the characteristics of mammograms of TNBC patients.…”
Section: Introductionmentioning
confidence: 93%
“…Medical image pattern recognition is another attractive field of research for image processing and machine-based prediction neural networks [29]. CNN architecture and image processing with texture feature parameters have been used in the classification of masses and normal tissue on mammograms with 90% accuracy [30, 31]. Detection of lung nodules, classification of radiograms and bone fractures has attracted many research attractions [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…[104][105][106][107] Besides the prediction of tumour malignancy, several radiomics studies examined the prediction of breast cancer molecular subtypes with the aim of leaving out liquid biopsies in the future. [108][109][110][111] Lymph node metastasis identification is an important prognostic factor and often determines treatment. In all clinically node negative patients, a sentinel lymph node procedure is the basis of the axillary treatment.…”
Section: Breastmentioning
confidence: 99%